Ексергетична ефективність місцевих автономних кондиціонерів - Лабай, В.; Дубіжанський, Д. (Видавництво Національного університету «Львівська політехніка», 2000)
In this article it was described the method of the exergetic analysis of one-step freon cooling engines, that are used in the local autonomous air conditioners . It was defined the exergetic output-input ratio of the several «split» air conditioners of firm «SANYO» for standard conditions and shown dependence of it from the air conditioner cooling capacity.